ANALYSIS OF VESICULAR BASALTS AND LAVA EMPLACEMENT PROCESSES FOR APPLICATION AS A PALEOBAROMETER/PALEOALTIMETER - Sahagian D.L.; Proussevitch A.A.; Carlson W.D. (My University, 2002)
We have developed a method for determining paleoelevations of highland areas on the basis of the vesicularity of lava flows. Vesicular lavas preserve a record of paleopressure at the time and place of emplacement because the difference in internal pressure in bubbles at the base and top of a lava flow depends on atmospheric pressure and lava flow thickness. At the top of the flow, the pressure is simply atmospheric pressure, while at the base, there is an additional contribution of hydrostatic lava overburden. Thus the modal size of the vesicle (bubble) population is larger at the top than at the bottom. This leads directly to paleoatmospheric pressure because the thickness of the flow can easily be measured in the field, and the vesicle sizes can now be accurately measured in the lab. Because our recently developed technique measures paleoatmospheric pressure, it is not subject to uncertainties stemming from the use of climate-sensitive proxies, although like all measurements, it has its own sources of potential error. Because measurement of flow thickness presupposes no inflation or deflation of the flow after the size distribution at the top and bottom is "frozen in," it is essential to identify preserved flows in the field that show clear signs of simple emplacement and solidification. This can be determined by the bulk vesicularity and size distribution as a function of stratigraphic position within the flow. By examining the stratigraphic variability of vesicularity, we can thus reconstruct emplacement processes. It is critical to be able to accurately measure the size distribution in collected samples from the tops and bottoms of flows because our method is based on the modal size of the vesicle population. Previous studies have used laborious and inefficient methods that did not allow for practical analysis of a large number of samples. Our recently developed analytical techniques involving high-resolution x-ray computed tomography (HRXCT) allow us to analyze the large number of samples required for reliable interpretations. Based on our ability to measure vesicle size to within 1.7% (by volume), a factor analysis of the sensitivity of the technique to atmospheric pressure provides an elevation to within about 400 m. If we assume sea level pressure and lapse rate have not changed significantly in Cenozoic time, then the difference between the paleoelevation "preserved" in the lavas and their present elevation reflects the amount of uplift or subsidence. Lava can be well dated, and therefore a suite of samples of various ages will constrain the timing of epeirogenic activity independent of climate, erosion rates, or any other environmental factors. We have tested our technique on basalts emplaced at known elevations at the base, flanks, and summit of Mauna Loa. The results of the analysis accurately reconstruct actual elevations, demonstrating the applicability of the technique. The tool we have developed can subsequently be applied to problematic areas such as the Colorado and Tibetan Plateaus to determine the history of uplift.